2023
DOI: 10.21203/rs.3.rs-2343709/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of river water quality assessment methods using the tree model and the nearest neighbor method (A case study: AhvazHydrometric Station)

Abstract: Ahwaz Hydrometric Station is responsible for controlling surface water resources and the Karoon River near Ahwaz city in southwestern Iran. And the present study aimed to determine the parameters affecting water quality, especially TH and SAR parameters. For this purpose, 39-year old statistical data were collected with 463 samples. To determine the water quality, first the correlation matrix method and statistical analysis were conducted, and then the correlation between them and the accuracy of these methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…The study showed the system's potential for real-time water quality parameter monitoring in precision agriculture. Another study by [13] monitored the water quality in a greenhouse tomato production system using an IoT-based system. The system was made up of temperature, electrical conductivity, dissolved oxygen, pH, and dissolved oxygen sensors that were linked to a central database.…”
Section: Review Of Iot In Agricultural Water Qualitymentioning
confidence: 99%
“…The study showed the system's potential for real-time water quality parameter monitoring in precision agriculture. Another study by [13] monitored the water quality in a greenhouse tomato production system using an IoT-based system. The system was made up of temperature, electrical conductivity, dissolved oxygen, pH, and dissolved oxygen sensors that were linked to a central database.…”
Section: Review Of Iot In Agricultural Water Qualitymentioning
confidence: 99%